HUBUNGAN KEBIASAAN MEROKOK DENGAN GANGGUAN PENDENGARAN AKIBAT BISING (NIHL) PADA PENERBANG PESAWAT ANGKUT TNI ANGKATAN UDARA YANG MELAKSANAKAN MEDICAL EXAMINATION DI LAKESPRA SARYANTO SELAMA TAHUN 2019 - Meta Marina Sudarman (Yayasan Pendidikan Medika Indonesia, 2024)
ABSTRACT Background : Smoking can cause a variety of diseases one of which is hearing loss. Nicotine causes the interruption of work on the nervous system, carbon monoxide nicotine works by increasing the hardening of the arteries and other circulatory problems, so that both are classified as ototoxic materials. Noise exposure can lead to the organ of corti damage, and decrease the blood flow to the cochlea resulting in cochlear hypoxia. Cigarette smoking could be ototoxic to cochlea, and could evoke cochlear ischemia. Cigarette smoking habit and noise exposure, each or together can cause hearing loss. Objective : To identify the correlation between cigarette smoking and noise induced hearing loss (NIHL). Methods : The design used is descriptive analytic study. Subjects were 106 pilots of the Indonesian Air Force transport community who had done medical examination at Lakespra dr. Saryanto and who had met the restrictive criteria. Results : From the 106 pilots, we found that the proportion of smoking habit with NIHL was 52,4%. Based on the Chi-Square test and Coefficient Contingency test showed there was not a significant difference and correlation between smoking habit and noise induced hearing loss with a significant p>0,05. Conclutions : There was not a significant correlation between cigarette smoking habit and noise induced hearing loss.